2023
DOI: 10.3389/fpls.2023.1121436
|View full text |Cite
|
Sign up to set email alerts
|

The combination of graphene oxide and preservatives can further improve the preservation of cut flowers

Abstract: It is reported that the use of nanomaterials can extend the vase life of fresh-cut flowers. Graphene oxide (GO) is one of these nanomaterials that aid in promoting water absorption and antioxidation during the preservation of fresh-cut flowers. In this investigation, the three mainstream brands of preservatives commercially available on the market (“Chrysal,” “Floralife,” and “Long Life”) in combination with low concentrations of GO (0.15 mg/L) were used to preserve fresh-cut roses. The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Consequently, this also suggests that the upgraded solution established by the addition of carbon nanomaterials to common preservatives (including carbohydrate and 8-hydroxyquinoline) may be more effective in improving the performance of cut flowers. Wu et al showed that the combination of 0.15 mg L −1 graphene oxide and preservative exhibited excellent antioxidant and moisture balancing ability, which could effectively prolong the vase life of fresh-cut roses [20]. Nevertheless, further validation in this direction needs to be pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this also suggests that the upgraded solution established by the addition of carbon nanomaterials to common preservatives (including carbohydrate and 8-hydroxyquinoline) may be more effective in improving the performance of cut flowers. Wu et al showed that the combination of 0.15 mg L −1 graphene oxide and preservative exhibited excellent antioxidant and moisture balancing ability, which could effectively prolong the vase life of fresh-cut roses [20]. Nevertheless, further validation in this direction needs to be pursued.…”
Section: Introductionmentioning
confidence: 99%